The Effect of Ability To Pay and Willingness To Pay on BPJS Premium Payment Compliance Among The Community in Mojosongo Surrounding, Surakarta - pratiwi, assilla; Aqsyari, Rizki; Setiani, Ditya Yankusuma; Kurniawan, Hendra Dwi (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2026)
The National Health Insurance (JKN) program managed by BPJS Kesehatan is an effort by the Indonesian government to achieve Universal Health Coverage (UHC). Since its implementation in 2014, BPJS Kesehatan has been facing financial deficits due to low participant compliance in paying premiums. Low Ability to pay and Willingness to pay, especially among low-income communities, as well as negative perceptions of service quality, are the main factors causing arrears. This condition has the potential to threaten the sustainability of the JKN program, so it is necessary to study the influence of ATP and WTP on participant compliance as a basis for formulating more targeted and data-based policies. Research Objectives. To determine the influence of Ability to pay and Willingness to pay on BPJS premium payment compliance in the community in Mojosongo Village, Surakarta. Research Design. This research is a quantitative study with a cross-sectional study design. Research Subjects. The subjects in the study were the community of Mojosongo Village, Surakarta with a population of 3,507 people. The number of samples in this study was 107 respondents using purposive sampling technique. Research Results. The results of this study indicate that the influence of Ability to pay increases compliance in paying BPJS premiums by (OR =3,156; CI 95%; 1.224 – 8.137, p = 0.017) was proven to be statistically significant and the influence of willingness to pay increased compliance in paying BPJS premiums by (OR = 6.902, CI 95% = 2.649 – 17.980, p = 0.001) was proven to be statistically significant. The most dominant influencing variable was willingness to pay (OR = 6.902, CI 95% = 2.649 – 17.980, p = 0.001).Conclusion: The results of this study indicate a relationship between ability to pay and willingness to pay on BPJS premium payment compliance, with willingness to pay being the most dominant variable influencing compliance. Keywords: Ability to pay, BPJS Health, JKN, Willingness to pay